Pengembangan Aplikasi Pemantauan Covid 19 Berbasis Web dan Mobile Menggunakan Metode Waterfall - Fanza Arga Pradana; Irma Handayani (TEMATIK, 2023)
The 2019-2020 coronavirus pandemic, commonly known as Covid-19, stands for corona virus disease 2019. It is a disease epidemic event caused by a novel coronavirus called SARS-CoV-2, originally named novel coronavirus 2019-nCov. From March 11 to May 16, 2020, a total of 4,434,653 Covid-19 cases were reported worldwide in more than 216 countries and territories, resulting in more than 302,169 deaths and more than 781,109 recoveries. The main problem is the lack of information and data on the distribution of Covid-19, with the covid19 distribution API can be used as a reference to find out information about covid19. But there are still many people who don't know it, in this case the role of information technology (IT) is needed. These APIs can be visualized in the covid-19 monitoring application using the REST API method. The data can be visualized in the form of a list on a covid-19 monitoring system using the HTTP protocol using the PHP programming language as a web and android with the Kotlin programming language. This system development uses the waterfall method, namely requirements analysis, system design, program code writing, program testing and program implementation. The result of this research is the development of an application to monitor the distribution of covid-19 by implementing the REST method and can be accessed by the public so that information about the distribution of covid-19 can be known more widely.